Pemberdayaan Kelompok Tani Suka Maju di Desa Ida Manggala Melalui Inovasi Pupuk Organik Padat Berbasis Limbah Lokal: Empowering the Suka Maju Farmers Group in Ida Manggala Village Through Innovation of Solid Organic Fertilizer Based on Local Waste - Rabiatul Wahdah; Nurin Nisa Farah Diena; Akhmad Gazali; Royana Firda Widya; Ahmad Candra Mulia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Environmentally friendly agriculture is increasingly needed to reduce dependence on inorganic fertilizers. Ida Manggala Village, Sungai Raya District, Hulu Sungai Selatan Regency has great potential for the development of organic rice farming; however, farmers still lack knowledge in processing livestock manure and agricultural residues into solid organic fertilizer. This community service program aimed to enhance farmers' capacity through training and mentoring in producing high-quality organic fertilizer from local waste using a semi-anaerobic composting method. The program consisted of socialization, training, hands-on practice, mentoring, and evaluation. Evaluation was conducted through pre- and post-tests to measure knowledge improvement and through visual assessment of compost quality (temperature, color, texture, pH, and moisture). The results showed an increase in farmers' understanding of composting techniques, from an average of 29% to 87% after the training. The compost produced met the physical criteria of the Indonesian National Standard (SNI 19-7030-2004), with a dark brown color, soil-like texture, odorless condition, a stable temperature of 29–30°C, and a neutral pH. This program successfully improved farmers' skills in using organic waste while supporting sustainable, environmentally friendly rice farming.